1999
DOI: 10.1161/01.str.30.12.2735
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Cerebrovascular and Metabolic Responses in the Delayed Phases of Injury After Transient Cerebral Ischemia in Fetal Sheep

Abstract: Background and Purpose-Perinatal hypoxic-ischemic injuries can trigger a cascade of events leading to delayed deterioration and cell death several hours later. The objective of this study was to characterize the cerebral blood flow responses and the changes in extracellular glucose and lactate during the delayed phases of injury and to determine their relationships with the pathophysiological events after hypoxic-ischemic injury. Methods-Two groups of near-term chronically instrumented fetal sheep were subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…In the immature fetus, shorter periods of ischemia than used here caused damage primarily to subcortical white matter Raad et al, 1999). PVWM lesions were infrequently detected in midgestation models of hypoxemia, where a restriction in uteroplacental blood flow resulted in decreased oxygen delivery and mild acidemia to the fetus without systemic hypotension or cerebral hypoperfusion (Rees et al, 1997(Rees et al, , 1999Mallard et al, 1998).…”
Section: Role Of Cerebral Ischemia In Pvwm Injurymentioning
confidence: 77%
See 2 more Smart Citations
“…In the immature fetus, shorter periods of ischemia than used here caused damage primarily to subcortical white matter Raad et al, 1999). PVWM lesions were infrequently detected in midgestation models of hypoxemia, where a restriction in uteroplacental blood flow resulted in decreased oxygen delivery and mild acidemia to the fetus without systemic hypotension or cerebral hypoperfusion (Rees et al, 1997(Rees et al, , 1999Mallard et al, 1998).…”
Section: Role Of Cerebral Ischemia In Pvwm Injurymentioning
confidence: 77%
“…We took several departures from previous approaches (Penning et al, 1994;Mallard et al, 1998;Reddy et al, 1998;Matsuda et al, 1999;Raad et al, 1999;Petersson et al, 2002) to develop a model of selective PVWM injury. To identify potential target populations of preOLs, we defined OL lineage maturation in the immature ovine brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These experimental studies support that a complex interplay of factors related to cerebrovascular immaturity predispose preterm cerebral white matter to injury from hypoxia-ischemia. Studies of global cerebral hypoperfusion found that the mid-gestation animal displayed a predilection to subcortical WMI, whereas the near term animal displayed predominantly parasagittal cortical neuronal injury [65,87]. A variable degree of WMI was also detected after systemic hypotension arising from intermittent or partial umblical cord occlusion [88,89].…”
Section: Hypoxia-ischemia In Fetal Sheep Generates Pathological Featumentioning
confidence: 99%
“…33,34 The immature ovine brain is also similar to preterm humans between 24 to 28 weeks in terms of the completion of neurogenesis, the onset of cerebral sulcation, the detection of the cortical component of the auditory and somatosensory evoked potentials, and an increased predilection for white matter injury. [35][36][37][38] Thus, the cephalically hypotensive immature ovine fetus appears to be particularly susceptible to hypoxia-ischemia, but prior studies provided no data regarding blood flow to periventricular white matter.…”
Section: The Vascular End-zone Hypothesismentioning
confidence: 99%